Problems Of Many-Valued Logic from The Point of View of The Theory of Socio-Cultural Code - Ibragim, Suleimenov; Oleg, Gabrielyan; Yelizaveta, Vitulyova, (Journal of Ecohumanism, 2024)
It is shown that there are prerequisites for returning to the original interpretation of logic as the science of the laws of thought. Using the methods of the neural network theory of the noosphere, it is proved that the nature of thinking is significantly influenced by the socio-cultural code of the ethnic/social system. A connection is revealed between philosophical categories as basic undefined concepts and archetypes, understood according to Jung. It is proved that the formalization of the laws of thinking, built on multi-valued logic, should operate not only and not so much with the concepts of natural language, but with “reflection quanta” lying on the archetypal level of consciousness. It is shown that the category of truth underlying classical logic can also be interpreted as a “reflection quantum”, but which has undergone a formalization procedure. It is demonstrated how exactly the apparatus of multi-valued logic can be applied to identifying links between the "quanta of reflection", which can be considered as a generalization of the rules of reasoning established in classical logic, dating back to Aristotle. The category “Qi”, which underlies ancient Chinese philosophy and is inseparable from the Chinese sociocultural code, was used as an example. Meaning of this category in the version that is assimilated by European and Eurasian sociocultural codes is revealed.